Salty dogs - Fogle, Jean M. (Wiley, 2007)
Engaging photos show dogs swimming, playing, romping, surfing, and lounging in the water and on the sand. Featuring dogs of varying pedigrees and personalities, including German Shepherds, Golden Retrievers, mutts, and the photographer's own beloved Jack Russell Terrier, this book captures and preserves utter, unadulterated canine bliss and spontaneity.